ANTI-OXIDANT POTENTIAL OF BAEL {AEGLE MARMELOS (L) CORR} FRUIT IN EXPERIMENTAL GASTRIC ULCERATED RAT - Madhu, *Singh; Kamleshwar, Prasad; Amit Kumar, Shukla (International Journal of Ayurveda and Pharma Research, 2016)
The present investigation of unripe fruit of A. marmelos was done to the study their antioxidant and free radical scavenger activity in experimental gastric ulcerated animals. The rats were given EtOH extract of herbal drug Aegle marmelos fruit extract (50 to 200 mg/kg) and control drug ranitidine (50 mg/kg) orally, twice daily for 5 days and on day 6 of experiment, 1 hour prior to subjecting the animal to stress or necrotizing concentration of respective irritants. Rats were then subjected to CRS in the absence and presence of cytoprotective irritant or herbal drugs. The fundic part of the stomach is homogenized (5%) in ice cold 0.9% saline with a Potter-Elvehjem glass homogenizer for 30 sec. the homogenate were centrifuged at 8,000 rpm for 10 min followed by centrifugation of the supernatant at 12000 rpm for 15 min in a sigma laboratory centrifuges 3K30 and the obtained mitochondrial fraction and further this fraction was used for the estimation of LPO product malondialdehyde. Further SOD and CAT was estimated.The study revealed that the 50% fruit extract dose dependently protected the oxidative stress and showed a tendency to decrease in volume acid-pepsin concentration and output. Reference drug rantidine a known cytoprotective agent has little effect on volume acid and pepsin concentration and acid output but showed a significant reduced in peptic output reduced LPO level and increase SOD and CAT level. The outcome indicate that the 50% ethanolic extract of A. marmelos fruit might have protected the rat tissues from ASP, PL, CRS and alcohol induced oxidative stress through anti-oxidant mechanism.